Religious Education 5.0: Concept, Design, and Implementation of Adaptive Pedagogy in Islamic Religious Education for the Society 5.0 Era - Firnando, Hero Gefthi; Khair, Nurul; Setiawati, Cucu (Indonesian Journal of Islamic Educational Review, 2025)
This study explores the development of pedagogical models in Islamic Religious Education (PAI) that harmoniously integrate spiritual grounding, contextual adaptability, and technological enhancement in the Society 5.0 era. Employing a mixed-methods approach, it combines philosophical analysis from classical Islamic scholars (Al-Ghazali, Ibn Khaldun) and modern educational theorists (Vygotsky, Fullan) with Design-Based Research (DBR) for instructional development. The research is conducted in three stages: (1) conceptualizing the core attributes of Religious Education 5.0, (2) designing adaptive learning modules incorporating blended learning, digital storytelling, and interfaith dialogue, and (3) evaluating their pedagogical impact through qualitative case studies and thematic analysis. The findings reveal notable improvements in student engagement, the internalization of Islamic values, and the development of interreligious empathy. The study presents a validated, transformative PAI model that is spiritually grounded, contextually relevant, and technologically responsive, contributing to the advancement of religious education in the digital era.